FAULT DIAGNOSIS OF INDUCTION MOTOR - Malhotra, Sanjana; Soni, M. K. (European Scientific Journal, ESJ, 2013)
Although, Induction motors are highly reliable, they are susceptible to many types of faults that can became catastrophic and cause production shutdowns, personal injuries, and waste of raw material. Induction motor faults can be detected in an initial stage in order to prevent the complete failure of the system and unexpected production costs. The purpose of this paper is the analysis of various faults of inverter fed induction machine. The laboratory tests thus conducted have been reported, and it is hoped that the research investigations reported would be very useful to the Power Electronics circuit industry.